Cytokine/chemokine levels in the CSF and serum of anti-NMDAR encephalitis: A systematic review and meta-analysis - Ma, Yushan; Wang, Jierui; Guo, Shuo; Meng, Zirui; Ren, Yan; Xie, Yi; Wang, Minjin (Frontiers in Immunology, 2023)
Abstract Objectives: To summarize the cytokines/chemokines levels of NMDAR-E and explore the potential role of these molecules and immune cells in the pathogenic mechanism. Methods: PubMed, Cochrane Library, Embase, and Web of Science databases were searched for the various articles that assessed concentrations of cytokines/chemokines in unstimulated CSF or serum in patients with NMDAR-E for this systematic review and meta-analysis. Standardized mead difference (SMD) and 95% confidence intervals (CI) were calculated by Stata17.0. Results: A total of 19 articles were included in the systematic review from 260 candidate papers, and cytokines/chemokines levels reported in CSF/serum were examined in each article. This meta-analysis included 17 eligible studies comprising 579 patients with NMDAR-E, 367 patients with non-inflammatory neurological disorders, and 42 healthy controls from China, Spain, South Korea, Australia, Czech, and Sweden. The results indicated that the levels of different cytokines IL-6, TNF-α, IL-10, IL-13, IL-1β, IL-12, and IL-17, and chemokine CXCL10 in CSF were significantly higher in NMDAR-E patients with large effect size. In addition, BAFF, CXCL13, and IFN-γ levels in CSF were higher in NMDAR-E patients with middle effect size. In contrast, levels of IL-2, IL-4 in CSF, and CXCL13 as well as BAFF in serum did not show a significant difference between cases and controls. Conclusions: These analyses showed that the central immune response in NMDAR-E is a process that involves multiple immune cell interactions mediated by cytokines/chemokines, and T cells play an important role in the pathogenesis of immunity.